Analisis Determinan GCG Dalam Mengatasi Pembiayaan Bermasalah di Bank Muamalat Indonesia Dengan Menggunakan Ukuran Self-Assessment 2017-2022 - Daulay, M Iqbal; Hasibuan, M. Idris; Trinanda, Ersa; Nursaputri, Laila (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Sharia banking is a financial institution whose operational principles are based on the Al-Qur'an and Hadith as well as the provisions and decisions of the National Sharia Fatwa Council of the Indonesian Ulema Council (DSN-MUI). Likewise, Good Corporate Governance (GCG) is a very important element in every line of management in a company. A large and technologically sophisticated company without a Good Corporate Governance (GCG) system will not allow the company to last long in glory. The implementation of Good Corporate Governance in sharia banking is carried out to increase and maintain public trust in sharia banks as institutions of trust and intermediation, protect stakeholders, and increase company values. In this research, researchers will use descriptive qualitative research by analyzing the determinants of GCG in overcoming financing problems at Bank Muamalat Indonesia using self-assessment measures 2017-2022.